2011
DOI: 10.1097/bcr.0b013e318217f83a
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Diagnoses After Hospitalization With Work-Related Burn Injuries in Washington State

Abstract: This study aims to describe workers who were hospitalized with work-related burn injuries and their psychiatric sequelae in Washington State. Psychiatric sequelae of interest were depression, posttraumatic stress disorder, and other anxiety disorders. Workers' compensation claims meeting a definition for a hospitalized burn patient from Washington State from January 2001 through April 2008 were analyzed. The resulting claims were searched for the presence of certain psychiatric diagnoses or treatment codes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The mean total healthcare cost per burn patient (85 studies) was $76,497 (range of $102–$717,306; median of $36,696) . The range includes costs in different market economies and healthcare settings, and the majority of studies calculated acute burn hospitalization costs only.…”
Section: Resultsmentioning
confidence: 99%
“…The mean total healthcare cost per burn patient (85 studies) was $76,497 (range of $102–$717,306; median of $36,696) . The range includes costs in different market economies and healthcare settings, and the majority of studies calculated acute burn hospitalization costs only.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1.5% of burned workers were admitted to hospital, but this represented 5% of the costs incurred which were in excess of 5 million $US. Anderson et al (2011) showed that in Washington state, 10.3% of all burns were chemical skin injuries among 329 studied patients. Total cost for all studied patients was $US 872,089.00.…”
Section: Financial Cost Of Chemical Skin Injuriesmentioning
confidence: 95%
“…Total cost for all studied patients was $US 872,089.00. Medical costs were significantly higher when a co-morbid psychiatric diagnosis was made, and 62 of such patients accounted for 48% of the total cost (Anderson et al 2011).…”
Section: Financial Cost Of Chemical Skin Injuriesmentioning
confidence: 99%
“…A number of psychosocial difficulties such as depression [6][7][8][9][10][11], anxiety [6,9,12,13], difficulties sleeping [14], and trauma symptoms [5,6,8,9,15] can also accompany the physical impact of a burn. Patients with burn scarring can also encounter unwanted questions or staring from others which can lead to avoidance of activities which could draw attention to their scars, fear of being judged negatively by others, low social self-esteem and withdrawal from romantic relationships [16][17][18].…”
Section: Introductionmentioning
confidence: 99%